In situ optical emission spectroscopic investigations during arc plasma synthesis of iron oxide nanoparticles by thermal plasma - Banerjee, Indrani; Joshi, N. K.; Sahasrabudhe, S. N.; Kulkarni, Naveen V.; Karmakar, Soumen; Pasricha, R.; Ghorui, S.; Tak, Atul K.; Murthy, Shri P. S. S.; Bhoraskar, S. V.; Das, A. K. (IEEE Transactions on Plasma Science, 2006)
Investigations using in situ precursor spectroscopy during the growth of nanoparticles of iron oxide by thermal plasma induced gas phase condensation method have been shown to be useful for correlating the size of nanoparticles with existing plasma parameters. The relative abundance of ionized Fe species inside the plasma plume is seen to directly establish the relation between particle size, arc current, arc length, and ambient pressure of the reacting oxygen gas. The argon plasma from a transferred arc reactor is made to impinge on the anode that is allowed to vaporize and react with oxygen. The spectral line profiles of both Ar and Fe along the plasma column during the synthesis of nanoparticles have been proved to be useful in understanding the growth mechanism. Band intensities of FeO molecular states indicated the inverse relation with particle sizes that have been correlated to the two competitive processes in which energy is released, namely: 1) one involving the radiative transition and 2) the other that of the growth by coagulation. Atomic Boltzmann plots are used for estimating the temperatures of the zones, whereas particle sizes have been inferred using transmission electron microscopic measurements.
Keywords: plasma arc device; plasma-materials processing applications; spectroscopy

Irradiation effects of 12 eV oxygen ions on polyimide and fluorinated ethylene propylene - Majeed, Riyadh M A Abdul; Purohit, V. S.; Bhoraskar, S. V.; Mandale, A. B.; Bhoraskar, Vasant N. (Radiation Effects and Defects in Solids, 2006)
Polyimide (PI) and Fluorinated Ethylene Propylene (FEP) samples (15mm x 15mm x 50 mu m ) were exposed to atomic oxygen ions of average energy similar to 12 eV and flux similar to 5x10(13) ions cm(-2) s(-1) , produced in the Electron Cyclotron Resonance (ECR) plasma. The energy and the flux of the oxygen ions at different positions in the plasma were measured by a retarding field analyzer. The fluence of the oxygen ions was varied from sample to sample in the range of similar to 5x10(16) to 2x10(17) ions cm(-2) by changing the irradiation period. The pre- and the post-irradiated samples were characterized by the weight loss, Scanning Electron Microscopy (SEM), X-ray Photoelectron Spectroscopy (XPS), and Fourier Transform Infrared (FTIR) techniques. The weight of the PI and FEP samples decreased with increasing the ion fluence. However, the erosion yield for the PI is found to be higher, by almost a factor five, when compared with that of FEP. On the surface region of irradiated samples, the concentrations of the carbon, fluorine, and oxygen and their corresponding chemical bonds have changed appreciably. Moreover, blisters and nanoglobules were also observed even at a fluence of similar to 10(17) ions cm(-2) . This oxygen ion fluence is almost two orders of magnitude lower than that of the 5 eV atomic oxygen, which a satellite encounters in the space, at the low Earth orbit, during its mission period of about 7 years.
Keywords: atomic oxygen; ECR plasma; FEP; FTIR; Polyimide; SEM; weight loss; XPS

Influence of filler size and morphology in controlling the thermal emissivity of aluminium/polymer composites for space applications - Babrekar, Harshada A.; Kulkarni, Naveen V.; Jog, Jyoti Prakash; Mathe, Vikas L.; Bhoraskar, S. V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
The paper has addressed the problem of controlling the thermal emissivities from metal/polymer composites prepared by solution method. Aluminium is used as a filler and polystyrene as a polymer-matrix. Aluminium particles, with micrometer and nanometer dimensions having different morphologies, were employed. The values of emissivities were reduced when the coarse grains and flakes of aluminium were used as fillers, whereas, no significant change was observed when nano-aluminium was used in the composite. Dielectric dispersion for the composites was measured and the results are analysed in view of Fresnel relation. The differences in the values of dielectric constants, between the experimentally measured and those which can be predicted theoretically, are thought to arise from the interfacial polarization. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Camouflaging; Composite; dielectric constant; Infra-red; Thermal emissivity